Assessment of changes in vitamin content and morphological characteristics in strawberries modified with a pulsed electric field using chromatography and optical coherence tomography - Ewa Korzeniewska; Ilona Gałązka-Czarnecka; Joanna Sekulska-Nalewajko; Jarosław Gocławski; Tomasz Dróźdż; Paweł Kiełbasa (NFS Journal)
Vitamins B and C are crucial for maintaining human health, so it is important to develop effective methods to support their extraction from products of plant origin. The research conducted by the authors focused on modifying the content of these vitamins in dessert strawberries using a pulsed electric field (PEF) with an intensity of 1, 3 or 5 kV/cm. Experiments have shown that PEF treatment with an intensity of 1 kV/cm and 10 pulses for 10 s resulted in a significant improvement in vitamin content and extraction efficiency of vitamin C by 22 %, folic acid by 24 %, thiamine by more than 50 % and riboflavin by more than 60 %.Optical coherence tomography imaging revealed texture changes in fruit pulp under the influence of PEF, related to the release of additional vitamins detected by chromatography methods.Additionally, PEF treatment offers significant benefits in fruit processing, including improved dehydration characteristics, reduced time and energy required for freeze-drying, increased extraction efficiency, and potential improvements in bioactive compound content and antioxidant properties.The research results may have practical applications in the analytical determination of vitamins C and B by improving the extraction efficiency. Moreover, the use of the PEF method can be important for producers of fruit products (including strawberries), as it enables them to improve the nutritional value of their products.